2021
DOI: 10.1029/2020je006781
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐Periodic Variation of the Lower Equatorial Cloud Induced by Atmospheric Waves on Venus

Abstract: A quasi‐periodic variation of the lower cloud amount induced by atmospheric waves was reproduced in our Venus general circulation model for the first time. This result agrees well with previous 2.3‐μm infrared nightside measurements. The cloud amount variation is mainly caused by a temperature fluctuation with a period of ∼5.5 Earth days near the cloud base, which is associated with a Kelvin‐like gravity wave with a zonal wavenumber‐1 structure. Our result might be able to explain the mechanism of the periodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 40 publications
2
23
3
Order By: Relevance
“…(2020) and Ando et al. (2021), small‐scale disturbances with large vertical winds were predominant at 50 km levels and the vertical winds associated with the planetary‐scale Kelvin‐like waves were not isolated. The present result suggests that the lower clouds could be also affected by the Kelvin modes associated with the 5.8‐day and 4.8‐day waves.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…(2020) and Ando et al. (2021), small‐scale disturbances with large vertical winds were predominant at 50 km levels and the vertical winds associated with the planetary‐scale Kelvin‐like waves were not isolated. The present result suggests that the lower clouds could be also affected by the Kelvin modes associated with the 5.8‐day and 4.8‐day waves.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, Ando et al. (2021) showed that the lower clouds are mainly affected by temperature deviations associated with Kelvin‐like gravity waves trapped at the cloud bottom levels, using a Venus GCM with a simple cloud model. However, there are significant differences in the wave structures in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained trend of the zonal mean cloud distribution was consistent with the past observation (Haus et al, 2014), although the cloud top altitude was the highest in high latitudes. The subsequent work by Ando et al (2021) investigated the temporal and spatial variation of the clouds in low latitudes and reported that the temperature variation associated with the Kelvin-like gravity wave causes the quasi-periodic cloud variation similar to that reported by Crisp et al (1991). They suggested that the temperature variation changes H 2 SO 4 saturation vapor pressure, and cloud condensation/evaporation occurs near the cloud base.…”
mentioning
confidence: 62%